STUDY OF THE EFFICIENCY OF SPANISH AIRLINES: A NON-PARAMETRIC DATA ENVELOPMENT ANALYSIS - Cifuentes-Faura, Javier (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2021)
Spain is an eminently tourist country, which allows the creation of countless jobs and contributes greatly to GDP growth. Millions of people visit this country every year, and more than 80% do so through air transport. This paper studies whether the 13 Spanish airlines with the highest revenues in 2018 were efficient in that year, thus filling a gap in the tourism literature. For this purpose, the non-parametric DEA technique has been used, using as inputs the total number of workers in the company and the total number of seats available (airline capacity). Total revenue and number of passengers have been used as outputs. The results obtained show that all the airlines studied within the IAG group (Iberia, Vueling, Air Nostrum, Iberia Express) are efficient, in addition to the Canary Islands airlines (Binter Canarias, Canarias Airlines and Canary Fly) and Air Europa. Likewise, the reference airlines for the inefficient ones have been determined, which will have to reduce the number of workers or make changes in capacity in order to achieve greater income and be efficient.